Implementing the OIE standards - addressing regional expectations (OIE ParisFR, 2014)
Highlights the challenges faced by OIE Member countries when implementing OIE animal welfare standards, and the willingness of the OIE, working in collaboration with governments and donors, to provide support for standard implementation within the framework of its global capacity-building initiatives.
Keywords: ANIMAL HEALTH